Enhanced CO2 Electroreduction on Neighboring Zn/Co Monomers by Electronic Effect. Issue 31 (28th April 2020) - Zhu, Wenjin; Zhang, Lei; Liu, Sihang; Li, Ang; Yuan, Xintong; Hu, Congling; Zhang, Gong; Deng, Wanyu; Zang, Ketao; Luo, Jun; Zhu, Yuanmin; Gu, Meng; et al.
Abstract: It is of great significance to reveal the detailed mechanism of neighboring effects between monomers, as they could not only affect the intermediate bonding but also change the reaction pathway. This paper describes the electronic effect between neighboring Zn/Co monomers effectively promoting CO2 electroreduction to CO. Zn and Co atoms coordinated on N doped carbon (ZnCoNC) show a CO faradaic efficiency of 93.2 % at −0.5 V versus RHE during a 30‐hours test. Extended X‐ray absorption fine structure measurements (EXAFS) indicated no direct metal–metal bonding and X‐ray absorption near‐edge structure (XANES) showed the electronic effect between Zn/Co monomers. In situ attenuated total reflection‐infrared spectroscopy (ATR‐IR) and density functional theory (DFT) calculations further revealed that the electronic effect between Zn/Co enhanced the *COOH intermediate bonding on Zn sites and thus promoted CO production. This work could act as a promising way to reveal the mechanism of neighboring monomers and to influence catalysis. Abstract : The electronic effect between neighboring Zn/Co monomers that effectively enhances the *COOH adsorption and thus boosts CO2 electroreduction to CO is described.